(untitled) (Modern education and development, 2025)
Inclusive insurance is a key tool in achieving financial inclusion and social protection for low-income populations. It aims to provide access to affordable, simple, and flexible insurance products for vulnerable and underserved segments of society. In developing countries, where large parts of the population are excluded from formal financial systems, inclusive insurance plays a crucial role in protecting livelihoods against various risks—such as health issues, natural disasters, and loss of income. Despite the potential benefits, the implementation of inclusive insurance in many countries, including Uzbekistan, is still at an early stage and requires systemic reforms, regulatory support, and cooperation among stakeholders. This paper explores the essence, principles, and global practices of inclusive insurance, and analyzes its current state and development prospects in Uzbekistan’s insurance market.